Model Latihan Teknik Tendangan Mawashi Geri pada Olahraga Katare - Yunus, Irfan; Hudain, Muh. Adnan; Dos Santos, Hezron Ahlim; Sudirman, Sudirman (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study aims to determine the effectiveness of the use of mawashi geri practice model on karate sports. This study employs a quantitative approach using a Research and Development (R&D) methodology. The subjects in this study are 60 karateka from the Inkanas dojo in Makassar City. The small group trial consists of 30 participants, the large group trial consists of 40 participants, and the effectiveness test involves 60 participants. The research instrument is divided into three assessment criteria: initial movement, execution movement, and final movement. Data collection techniques are conducted through observation. The data analysis technique uses the "T-Test" with a pre-experimental research design in the form of a one-group pretest-posttest design. The results of the prefix movement found that the mawashi geri kick start increased by 4.97 from the initial 16.86 to 21.83 with t-count is greater than t-table. On average the execution of the mawashi geri kick increased by 5.28 from the initial 15.63 to 20.91 with t-count is greater than the t-table. At the average end of the mawashi geri kick increased by 5.76 from the initial 13.75 to 19.51 with t-count is greater than t-table. Based on this, it can be stated that this mawashi geri kick model can improve the ability of kick mawashi geri for karateka in Dojo Inkanas of South Sulawesi.